Dialog religii z nauką wyzwaniem dla chrześcijaństwa - Leciejewski, Sławomir (Człowiek i Społeczeństwo, 2022)
Source literature lists several versions of creationism as well as numerous manners of understand- ing evolutionism. Creationist views may be limited to four basic ones: fundamentalist creationism, creation science, intelligent design and evolutionary creationism. In my article I will justify which of these versions of creationism may be considered as dialoguing with science, and which of them turn out, to a greater or lesser degree, unable to enter into this dialogue. I will answer the question how creationism should be understood in order for it to be able to engage in a debate with modern science. In other words, the central question of this article will be: how is the dialogue between religion (creationism) and science (evolutionism) feasible?